AN ANALYSIS OF THE ROLE OF CONSUMER VALUE, BROWSING ACTIVITY, AND IMPULSIVENESS AMONG E-COMMERCE USERS IN RIAU PROVINCE - Rianda Kapri; Awliya Afwa; Moniko Moniko; Hamanda Hadi Saputra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the effect of utilitarian value and hedonic value of online reviews on browsing activity, urge to buy impulsively, and impulse buying behavior among Gen-Z consumers in Riau Province, with impulsiveness as a moderating variable. The study employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4, based on data from 105 respondents. The results indicate that utilitarian value and hedonic value have a significant effect on browsing (β = 0.344 and β = 0.273; p < 0.01), browsing significantly affects urge to buy impulsively (β = 0.452; p < 0.001), and urge to buy impulsively significantly affects impulse buying behavior (β = 0.584; p < 0.001). The moderating effect of impulsiveness is partially supported, where individuals with high impulsivity are more responsive to emotionally driven reviews than informational ones.These findings affirm that online reviews function as cognitive and affective triggers in digital consumption behavior. Gen-Z exhibits browsing tendencies driven by enjoyment and curiosity, ultimately encouraging spontaneous purchases. Practically, the results offer implications for digital marketers to balance informational credibility and emotional appeal in ethical and sustainable online marketing communication strategies